2012
DOI: 10.1097/mco.0b013e328357f747
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and nonalcoholic fatty liver disease

Abstract: Purpose of review Oxidative stress plays a central role in the transition from simple steatosis to nonalcoholic steatohepatitis (NASH). An effective therapeutic strategy is to target reduction in oxidative stress in NASH patients. The aim of this review is to discuss the role of oxidative stress in NASH and biological activities of vitamin E and present available evidence on the therapeutic efficacy of vitamin E in NASH. Recent findings In Pioglitazone versus Vitamin E versus Placebo for the Treatment of Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 60 publications
1
58
0
1
Order By: Relevance
“…We and others (5,31,32) have shown that toxininduced steatohepatitis models produce metabolic oxidative stress. The toxin-and diet-induced steatohepatitic injury models that produce metabolic oxidative stress are relevant to clinical outcomes because patients with NASH show oxidative stress and have been hypothesized to augment disease progression (27). Our results demonstrate that CYP2E1 increases lipid peroxidation and oxidative and nitrosative stress upon steatohepatitic injury.…”
Section: Steatohepatitic Injury In Obese Mice Is Associated With Incrsupporting
confidence: 50%
“…We and others (5,31,32) have shown that toxininduced steatohepatitis models produce metabolic oxidative stress. The toxin-and diet-induced steatohepatitic injury models that produce metabolic oxidative stress are relevant to clinical outcomes because patients with NASH show oxidative stress and have been hypothesized to augment disease progression (27). Our results demonstrate that CYP2E1 increases lipid peroxidation and oxidative and nitrosative stress upon steatohepatitic injury.…”
Section: Steatohepatitic Injury In Obese Mice Is Associated With Incrsupporting
confidence: 50%
“…Oxidative stress originating from mitochondria and cytochrome P450 2E1 is considered as a key signal in the pathophysiology of NASH (34,35). Interestingly, studies in animal models and patients show that antioxidants, such as vitamin C, vitamin E, and N-acetylcysteine (NAC), are useful for both protecting against NAFLD and treating this disease (36)(37)(38). ROS affect several cell signaling pathways involved in cell proliferation and tumorigenicity (39,40).…”
Section: Introductionmentioning
confidence: 99%
“…The TONIC randomized controlled trial showed that neither vitamin E nor metformin are superior to placebo in sustaining a reduction in ALT levels of pediatric NAFLD patients [31] . A recent review article concluded that vitamin E is only recommended in adults with NASH who do not have diabetes or cirrhosis, or an aggressive histology [32] . In a meta-analysis, adjuvant vitamin E was not shown to have a significant effect on normalizing serum ALT levels.…”
Section: Antioxidants Agentsmentioning
confidence: 99%